Noncoaxial multivortices in the complex sine-Gordon theory on the plane - Barashenkov, I. V.; Shchesnovich, V. S. [UNESP]; Adams, R. M. (IOP Publishing, 2002)
We construct explicit multivortex solutions for the complex sine-Gordon equation (the Lund-Regge model) in two Euclidean dimensions. Unlike the previously found (coaxial) multivortices, the new solutions comprise n single vortices placed at arbitrary positions (but confined within a finite part of the plane.) All multivortices, including the single vortex, have an infinite number of parameters. We also show that, in contrast to the coaxial complex sine-Gordon multivortices, the axially-symmetric solutions of the Ginzburg-Landau model (the stationary Gross-Pitaevskii equation) do not belong to a broader family of noncoaxial multivortex configurations.